Guts - Telgemeier, Raina (New York Graphix, 2019)
Tegneserie - graphic novel. Raina wakes up one night with a terrible upset stomach. Her mom has one, too, so it's probably just a bug. Raina eventually returns to school, where she's dealing with the usual highs and lows: friends, not-friends, and classmates who think the school year is just one long gross-out session. It soon becomes clear that Raina's tummy trouble isn't going away ... and it coincides with her worries about food, school, and changing friendships
Comic strips
1 2 13 23
Keywords: Children -- Physiology; Stomach -- Diseases; Stress in children